Misoprostol use in obstetrics - Chaves, Fabíola Augusta Marinho; Aragão, Julio Cesar Soares (Cadernos UniFOA, 2018)
This study is a bibliographic review in order to overview the use, indications and contraindications of misoprostol in obstetrics. Thirty three academic articles in Portuguese, Spanish, and English in the range 2005 to 2014 wer collected and analysed. Misoprostol is a methyl analogue of PGE1 and has anti-secretory action and protective properties of the mucosa, and cause increased uterine contractility, induce the development of contractions and cause cervical effacement, facilitating the expansion necessary to carry out obstetric procedures. It is an important drug in obstetric practice and is indicated for treatment of missed abortion, labor induction, shortens the operatory time in situations where the cervix has no dilation, reduce the frequency of complications and caesarean indications, and can be used in prophylaxis of post-partum hemorrhage. Attention should be paid to its misuse as an abortifacient and the existence of reports of congenital malformations, especially the Moebius Syndrome. It is a stable product, safe, effective, inexpensive and easy management, ensuring broad employability of its clinical use in current obstetrics.